Explication of the Relationship Between the Ministers & the Ministry & Christ (1 COR. 3:1-15): Contextual Understanding of Catholic Priests - Ezeogamba, Anthony Ezeogamba (International Journal of Culture and Religious Studies, 2023)
The Word became Flesh and dwelt among us (John 1:1-14). This Word is named Jesus Christ (Matt 1:21; Luke 1:31; 2:21). He took flesh and dwelt among us for the salvation of mankind (Matt. 1:21b). From the beginning, Jesus knew that the work of salvation has to go on from generation to generation and thus called people who would assist him to propagate the message even when he is no longer there physically. He thus selected disciples and out of the disciples he selected twelve ordinary men named apostles whose names and ministry appear in Matthew 10:2- 26. This shows that Jesus Christ is the one who calls, the one who owns the ministry, and the one who will reward each according to his or her contribution and based on the quality of the contributions. The greatest problem today is that some ministers have forgotten that the ministry does not belong to them and have no reason at all to quarrel with one another but should see one another as collaborators in Christ's ministry. Secondly, some people of God have forgotten that every minister has God-given talent which should not warrant them to be involved in a personality cult that is, preferring one minister over another or even preferring a minister to Jesus. This paper aims at explaining again who a minister is, how he should see his fellow minister, and how he should see Jesus Christ. The work adopts the Historical-Critical Method (HCM) as well as Textual Criticism (TC) to unravel the inner meaning of 1 Cor. 3:1-15. HCM is a branch of criticism that investigates the origins of ancient texts in order to understand the world behind the text - 1 Cor. 3:1-15. In the same way, TC was used so as to get to the original wording of the text as was written by Paul. The writer discovers that some ministers have forgotten their roles, their relationship with their fellow ministers, and with Jesus Christ, the owner of the ministry. The paper recommends, among other things, that there should be the adequate formation of candidates going into the ministry as priests as well as constant catechesis on the part of members of the Church, especially, on the nature of the Church. This will enable us to avoid unnecessary rivalry in the Church. As a matter of policy, this should be started as soon as a child reaches the age of reasoning. Hence, the saying, "catch them young." Significantly, this work will be of immense benefit to all the members of the Church as well as her ministers.